Studies to investigate the prevalence of estrogen receptor polymorphism & its association alveolar bone loss & early tooth loss in postmenopausal women - Rehman, Asia (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2006)
Depletion of estrogen production and secretion in postmenopausal women may lead to rapid bone loss and decreased bone mineral density (BMD). Decreased systemic BMD may also affect oral bone particularly mandibular bone resorption. Although several environmental factors influence bone loss, genetic contribution particularly estrogen receptor gene (ERG) polymorphism had been reported. The objectives of this study were to investigate the distribution of ERG polymorphisms in postmenopausal Malay women (PMW) and to detect the association of the polymorphisms to alveolar bone resorption. Sixty four PMW were recruited from the Out Patient Dental Clinic, Hospital Universiti Sains Malaysia, Kelantan. Oral examination and alveolar bone resorption measurement were performed on these study subjects. Genotyping was done through the restriction cleavage of polymerase chain reactionamplified genomic DNA with the two restriction enzymes, Pvull and Xbal. Estrogen receptor genotypes were represented as P or p (Pvull) and X or x (Xbal) with the lower case letters signifying the presence of the restriction site. The results of this study indicated a high frequency of heterozygous allelic variant (PpXx) in PMW. However no significant association between ERG polymorphisms and alveolar bone resorption was observed. Therefore ERG polymorphisms may not be a genetic marker for the alveolar bone resorption in PMW.